The spatial dispersion of seabirds near the South Orkney Islands and the Weddell-Scotia confluence - Veit, RR; Hunt, GL (Polar Biology, 1992)
We used five transects radiating from the South Orkney Islands to describe the distribution and abundance of marine birds during three days in late summer 1983. We found elevated numbers of birds at most crossings of steep physical gradients (fronts), but species were not equally attracted to each front. Our data suggest that the fronts around the South Orkney Islands, especially the Weddell-Scotia Confluence, provide important foraging habitat for birds. Albatrosses and fulmars appeared to aggregate preferentially near fronts overlying the insular slope, whereas Chinstrap Penguins were most abundant over the shelf. © 1992 Springer-Verlag.